Python Parallel and Concurrent Programming Part 1. - Chiu Stone, Olivia; Stone, Barron (linkedin.com, 2019)
Write more effective programs that execute multiple instructions simultaneously. Learn the fundamentals of parallel and concurrent programming in Python.